2018
DOI: 10.3389/fenrg.2018.00065
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Torrefied U.S. Waste Blends

Abstract: Power generation facilities in the U.S. are looking for a potential renewable fuel that is sustainable, low-cost, complies with environmental regulation standards and is a drop-in fuel in the existing infrastructure. Although torrefied woody biomass, meets most of these requirements, its high cost, due to the use of woody biomass, prevented its commercialization. Industrial waste blends, which are also mostly renewable, are suitable feedstock for torrefaction, and can be an economically viable solution, thus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The materials in this study were waste industrial paper wastes, MPW and commercially available LDPE (Rainier Plastics), cellulose powder (Avicel PH-101, ∼50 µm particle size, Fluka) as well as hemicellulose (extracted xylan). The paper wastes and MPW have been described in detail in the prior studies (Xu et al, 2018;Xu et al, 2020). The paper wastes are a mixture of paper, carton and cardboard, label matrix residuals, wax papers, and laminated non-recyclable papers; and the plastic wastes consist of LDPE, PE, polyethylene-terephthalate (PET), polyamide-nylon, polyvinylchloride (PVC), PP, and some other materials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The materials in this study were waste industrial paper wastes, MPW and commercially available LDPE (Rainier Plastics), cellulose powder (Avicel PH-101, ∼50 µm particle size, Fluka) as well as hemicellulose (extracted xylan). The paper wastes and MPW have been described in detail in the prior studies (Xu et al, 2018;Xu et al, 2020). The paper wastes are a mixture of paper, carton and cardboard, label matrix residuals, wax papers, and laminated non-recyclable papers; and the plastic wastes consist of LDPE, PE, polyethylene-terephthalate (PET), polyamide-nylon, polyvinylchloride (PVC), PP, and some other materials.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the heat convection from the oven to the sample surface is much slower than the heat conduction into the sample; for M << 1, it indicates that the heat conduction into the sample is much faster than the reaction rate. Thus, the particle temperature throughout was uniform and equals to the gas temperature (which is measured), and the reaction rate was governed by the heat convection from the oven to the surface of the sample (Xu et al, 2018).…”
Section: Heat Transfer Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that we will flow fiber and plastic flakes that are 10×10 mm, with a thickness of <1 mm into the reactor. We also note that when either fiber and plastic flakes are torrefied they become very brittle as seen by Zhuo et al [93] and can be grinded rather easily by the paddles that act as blades. Indeed, in the 1inch reactor (as well as in the batch reactor) the char was in the form of a very fine powder.…”
Section: Continuous Paddlesupporting
confidence: 55%
“…Xu et al (2018) [92] studied physical properties of various waste material blends after their torrefaction in a convective furnace at 300 • C and exposure time of 3 to 120 min. They concluded that, depending on the material type, its heating value remained the same or increased, and the material loss was up to 55%.…”
Section: Biomass Pretreatmentmentioning
confidence: 99%